2020
DOI: 10.3126/jcmsn.v16i2.28660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Endoscopic Findings in Patients undergoing Colonoscopy at a Tertiary Care Centre of Central Nepal

Abstract: Background: Colonoscopy is an invasive procedure used for both diagnostic and therapeutic purpose for detection and management of the diseases of rectum, colon, and terminal ileum. This study was undertaken to assess the clinical profile and endoscopic findings in patients undergoing colonoscopy.    Methods: One hundred and sixty patients underwent colonoscopy from January 2018 till  December 2019.  Clinical profile, endoscopy and histological findings were studied from the hospital departmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our results were supported by Bhattarai and Acharya [7] who revealed that the commonest indications for performing colonoscopy were chronic diarrhea, altered bowel habits, chronic abdominal pain and bleeding per rectum. Furthermore, Benhamdane et al [8] revealed that the most common indications for pathological colonoscopy were: rectal bleeding, diarrhea, constipation, iron deficiency anemia and melena.…”
Section: Discussionsupporting
confidence: 87%
“…Our results were supported by Bhattarai and Acharya [7] who revealed that the commonest indications for performing colonoscopy were chronic diarrhea, altered bowel habits, chronic abdominal pain and bleeding per rectum. Furthermore, Benhamdane et al [8] revealed that the most common indications for pathological colonoscopy were: rectal bleeding, diarrhea, constipation, iron deficiency anemia and melena.…”
Section: Discussionsupporting
confidence: 87%
“…The sample size was calculated based on the standard formula 9 for cross-sectional studies n =Z 2 a/2 *P*(1−P)/d 2 , where Z a/2 was 1.96 for 95% level of confidence, P is the estimated proportion of prevalence of primary outcome and d is the desired level of precision which was set at 0.02. The prevalence proportion (P) was considered to be 6.48% 4 , and thus, the total sample size study required was 642, including an additional 10% to avoid errors. A convenience sampling method was implemented to select participants.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the importance of colonoscopy in clinical practice, only a few studies have described patients undergoing colonoscopy in Nepal 4 7 . In this study, we aim to evaluate the demographic characteristics, clinical presentation, colonoscopy observations and histological findings of patients undergoing colonoscopy by analyzing the records at a tertiary care hospital in Nepal.…”
Section: Introductionmentioning
confidence: 99%